Home and workplace smoking bans in Italy, Ireland, Sweden, France, and the Czech Republic - Heck, Julia E. (Eur Respir J, 2009)
The purpose of this study was to report predictors and prevalence of home and workplace smoking bans in 5 European countries. We conducted a population-based telephone survey of 4977 women, ascertaining factors associated with smoking bans. Odds ratios (ORs) and 95% confidence intervals (CI) were derived using unconditional logistic regression. A complete home smoking ban was reported by 59.5% of French, 63.5% of Irish, 61.3% of Italian, 74.4% of Czech, and 87.0% of Swedish women. Home smoking bans were associated with younger age and being bothered by secondhand smoke, and among smokers, inversely associated with greater tobacco dependence. Among nonsmokers, bans were also related to believing smoking is harmful (OR=1.20, CI: 1.11, 1.30) and having parents who smoke (OR=0.62, CI: 0.52, 0.73). Workplace bans were reported by 92.6% of French, 96.5% of Irish, 77.9% of Italian, 79.1% of Czech, and 88.1% of Swedish women. Workplace smoking bans were reported less often among those in technical positions (OR=0.64, CI: 0.50, 0.82) and among skilled workers (OR=0.53, CI: 0.32, 0.88) than among professional workers. Workplace smoking bans are in place for most workers in these countries. Having a home smoking ban was based on smoking behavior, demographics, beliefs, and personal preference.